Responsibility endowing power: A theoretical framework of health empowerment for Chinese older people with chronic illness - Heng Zhang; Hao Zhang; Jie Peng (Wiley, 2024)
Abstract Aim To construct a health empowerment framework for the Chinese older people with chronic conditions. Design A Straussian grounded theory design was selected to generate the theoretical framework. Methods Data were collected from 53 community‐dwelling older people with chronic conditions in China between November 2017 and August 2019, via semi‐structured interviews and with participating observation. The constant comparative method identified the key categories. Results 'Responsibility endowing power', the health empowerment core theme, was defined as initiating, performing and realizing responsibility towards health through the interaction between the self, family and society. The framework enriches the meaning of health empowerment, changing older people's nursing practice.